Tantangan dan Peluang dalam Adopsi Teknologi Digital pada Usaha Mikro, Kecil, dan Menengah (UMKM) di Jakarta - Sarah Anistia; Kharisma Azmi Yoningsih (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2026)
In globalization and evolving consumer behavior, ( Micro, Small, and Medium Enterprises) MSMEs must embrace digital technology to endure and remain competitive. This study aims to investigate the challenges and opportunities faced MSMEs in Jakarta in adopting digital technology utilizing the Diffusion of Innovation (DOI) theory framework.  The methodology is using in-depth interviews with 25 MSMEs across diverse sectors. The analysis indicates that relative advantage is the primary motivator, as MSMEs stakeholders perceive digital technology to enhance market access, operational efficiency, marketing strategies, product innovation, and increase competitiveness and business sustainability. However, the technology's compatibility with the local work culture is not aligned, indicating that the drive to innovate is stronger. The opportunity to evaluate technology positively impacts adoption decisions. This study enhances comprehension of the dynamic’s digital technology adoption by MSMEs.